Public support for the media: A six-country overview of direct and indirect subsidies - Nielsen, R; Linnebank, G (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2011)
This report examines the main forms of direct and indirect public sector support for the media in six developed democracies (Finland, France, Germany, Italy, the United Kingdom, and the United States), shows how the main beneficiaries of the hundreds of millions of Euros worth of subsidies provided remain broadcast and print industry incumbents, and discusses the prospects for reform.